Tumour gene therapy using adenoviral vectors expressing tumour necrosis factor alpha - Marr, Anthony Robert (My University, 1999)
The general focus of my project was the production of recombinant adenovirus vectors for use in inmmunotherapy of cancer. The basic strategy involved the infection of tumour cells with Ad-vectors expressing cytokines, inducing a local anti-tumour response. The cytokine of interest for my project was tumour necrosis factor alpha (TNFα), which I used for treatment of a murine transgenic model of breast cancer. TNFα is a pluripotent cytokine with a wide variety of physiological functions including antitumour activity. TNFα was originally discovered through the anticancer activity of sera of mice treated with endotoxin (Carswell et al., 1975). There are two known cell surface receptors for TNFα termed p55 and p75. Both receptors signal a variety of functions and some redundancy exists between them. However the p55 TNF receptor is the major activator of cytotoxicity and cytokine secretion, while the p75 TNF receptor is primarily responsible for proinflammatory and lymphoproliferative signals. Perhaps the major limiting factor affecting the use of TNFα in tumour therapy is its systemic toxicity, through the induction of septic shock and cachexia (Tracey, 1995; Tracey et al., 1986). We have been investigating techniques which would reduce the systemic side effects of TNFα, while retaining its antitumour activity. We found that local expression of TNFα from within a tumour (transduced cells) alone is not enough to eliminate its lethal side effects, therefore two other approaches are being investigated in an attempt to deal with systemic toxicity induced by TNFα. The first was the construction of an Ad vector expressing a membrane bound mutant of murine TNFα (see chapter III). The second approach involved specific targeting of the two cell surface receptors of TNFα. To accomplish this, we used Ad vectors expressing human TNFα, and a novel p75 TNF receptor specific mutant of murine TNFα for use in tumour immunotherapy (See chapters IV and V). It was found that restricting TNFα to the membrane produced a marked reduction in lethality while retaining near normal antitumour activity. Targeting the p55 TNF receptor proved to be ineffective, while targeting the p75 TNF receptor drastically reduced the lethality of the cytokine while retaining some antitumour activity. However the overall efficacy of this therapeutic technique was poor, as only a low percentage of mice were cured with our Ad-TNF vectors.
Keywords: Medical Sciences; Medical Sciences